An Investigation into Biodiversity Accounting: Evidence from the European Manufacturing Sector - Drae BENT; Elisabete VIEIRA; Mara MADALENO (Loka: Journal Of Environmental Sciences, 2023)
Purpose:This paper aims to contribute to the biodiversity literature by examining the biodiversity reporting practices of the top 100 manufacturing companies in the European Union.Methodology:This study uses content analysis to explore and investigate disclosure themes in sustainability reports (and equivalents) for 2019–2021.Findings:Descriptive statistics, frequency charts, and graphical representations of the data support the results. Biodiversity reporting is still limited but nascent. There was an increase in Biodiversity reporting from 2019 to 2021 during the COVID-19 pandemic, with more disclosure acceptance from the sampled companies. Contrary to expectations, larger companies showed little under-reporting compared to smaller manufacturing companies.Implication:These findings contribute to the discussion on biodiversity reporting practices, especially in the era of the COVID-19 pandemic. The results are helpful for policymakers, academic researchers, and stakeholders seeking to promote Biodiversity reporting in organizations.